2015
DOI: 10.1590/s0100-736x2015000500012
|View full text |Cite
|
Sign up to set email alerts
|

Babesia canis vogeli infection in dogs and ticks in the semiarid region of Pernambuco, Brazil

Abstract: Abstract:This study aimed to report the prevalence of Babesia canis vogeli in dogs and ticks in the urban and rural areas of Petrolina, Pernambuco. Serum and peripheral blood samples of 404 dogs were tested by indirect immunofluorescence assay (IFA) and by blood smears, respectively. The presence of tick infestation was evaluated, and some specimens were submitted to DNA amplification by polymerase chain reaction (PCR). The presence of antibodies anti-B. canis vogeli was determinate in 57.9% (234/404) of dogs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Among the etiologic agents of hemoparasitic infections, Ehrlichia canis, Anaplasma platys and Babesia vogeli are worthy of note due to their wide geographic distribution and high prevalence (Ramos et al 2009, Araújo et al 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the etiologic agents of hemoparasitic infections, Ehrlichia canis, Anaplasma platys and Babesia vogeli are worthy of note due to their wide geographic distribution and high prevalence (Ramos et al 2009, Araújo et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, molecular techniques are highly sensitive and specific and can accurately determine the infection status in dogs (Ramos et al 2009). In Brazil, the prevalence of these hemoparasites, determined by means of molecular methods, can vary from 1.6 to 55% for A. platys (Ramos et al 2009, Lasta et al 2013, Sousa et al 2013, from 16.4 to 57% for E. canis (Ramos et al 2009, Silva et al 2012a, Sousa et al 2013) and from 3.3 to 57.9% for B. vogeli (Jojima et al 2008, Sousa et al 2013, Araújo et al 2015, depending on the geographic region and the studied population.…”
Section: Introductionmentioning
confidence: 99%
“…Miranda et al (2008) obtained a positivity rate of 1.47% in dogs from Campos dos Goytacazes in the same state. Araújo et al (2015) found only two positive samples (0.5%) in rural Pernambuco. The lower sensitivity of optical microscopy used by these authors as well as in the presente study was evidenced by the low frequency of parasitic forms of piroplasm detected in blood smears, which can be explained by the fact that parasites are rarely found in the peripheral blood of animals with subclinical infection (Weiss & Wardrop, 2010).…”
Section: Resultsmentioning
confidence: 82%
“…Studies conducted in Campo Grande (Mato Grosso do Sul) showed a prevalence of 81.6% (Sousa et al, 2013), and in Ilha Solteira (São Paulo), 72% (Paulan et al, 2013). In Petrolina (Pernambuco), the prevalence was 57.9% (Araújo et al, 2015) and in Jaboticabal (São Paulo), it was 67% (Oliveira et al, 2008).…”
Section: Discussionmentioning
confidence: 98%